The Utilization of Virtual Reality Technology for First Aid Learning in Vocational High School Nursing Students: English - Widodo, Wahyu; Yosi Kristian (Institut Sains dan Teknologi Terpadu Surabaya (d/h Sekolah Tinggi Teknik Surabaya), 2025)
This VR application can be used to train nurses for future professional challenges they may face. The continuous development of VR applications enables trainees to effectively confront real-life simulations and experience increasingly concrete situations, which can be highly important in nursing education. The use of 3D visualization allows for study understanding of various activities and can help prevent potential errors in the future. Nursing education has always utilized simulation-based learning methods, which are widely recognized in nurse education. Skills laboratories have been established in recent years as a form of learning that provides skills and knowledge through repeated practice without requiring placement. This study discusses the utilization of virtual reality technology in first aid training. First aid training using VR technology is expected to increase the effectiveness of learning by at least 20%. The VR application for first aid learning consists of four first aid training modules, including treatment for burns, fractures, bleeding wounds, and breathing difficulties. This VR application was tested on students to determine whether it could improve the effectiveness of first aid learning. Based on the application testing using a respondent questionnaire, it was found that the assessment of knowledge enhancement in learning reached 72.08. Furthermore, this virtual reality application is more effective when used in first aid training, as evidenced by the superiority of the post-test scores of students who learned first aid using virtual reality compared to those who learned first aid without VR, which was 23.4%.